Financial entrepreneurial resources and economic factors of manufacturing SMEs in zone 5 Ecuador - Valero-Camino, Magdalena (2025)
SMEs sometimes face difficulties with their financial resources. Given this, this study aimed to identify how financial resources influence the economic factors of SMEs in the manufacturing sector of Zone 5 of Ecuador. A quantitative, exploratory, descriptive and field approach was adopted. The sample consisted of 353 companies in this zone. The results revealed a significant impact, where access and management of these resources are decisive for business success, influencing growth, profitability and competitiveness. 41.9% of respondents considered that the availability of financial capital greatly affects their performance. In addition, 25.8% recognized a significant relationship between access to bank loans and economic growth. It is concluded that it is crucial for SMEs to have access to financing, ongoing training, professional advice, and manage their investments efficiently and strategically